2017
DOI: 10.1038/s41598-017-13860-9
|View full text |Cite
|
Sign up to set email alerts
|

Florfenicol-induced Mitochondrial Dysfunction Suppresses Cell Proliferation and Autophagy in Fibroblasts

Abstract: Florfenicol (FLO) is one of the most popular antibiotics used in veterinary clinic and aquaculture. FLO can inhibit both bacterial and mitochondrial protein synthesis. However, the effects of FLO on mitochondrial function and cellular homeostasis remain unclear. Here we show that FLO inhibits expression of mitochondrial DNA-encoded proteins, decreases mitochondrial membrane potential, and promotes generation of reactive oxygen species (ROS) in vitro. As a result, activities of mitochondrial respiratory chain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
2
15
0
1
Order By: Relevance
“…Because of the similarities between mitochondrial and bacterial ribosomes, the antibiotics developed to inhibit bacterial ribosomes inevitably inhibit mitochondrial ribosomes, leading to mitochondrial damage ( Wang et al., 2015b ). Our previous reports showed that FLO inhibits the expression of mitochondrial DNA-encoded proteins, resulting in mitochondrial damage and dysfunction ( Hu et al., 2017 ). Mitochondria are eukaryotic cellular organelles specialized for energy conversion and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the similarities between mitochondrial and bacterial ribosomes, the antibiotics developed to inhibit bacterial ribosomes inevitably inhibit mitochondrial ribosomes, leading to mitochondrial damage ( Wang et al., 2015b ). Our previous reports showed that FLO inhibits the expression of mitochondrial DNA-encoded proteins, resulting in mitochondrial damage and dysfunction ( Hu et al., 2017 ). Mitochondria are eukaryotic cellular organelles specialized for energy conversion and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…El fl orfenicol afecta a nivel de la síntesis de proteínas a organelos de origen procariótico de la célula eucariótica (mitocondria y cloroplasto). Causa alteraciones estructurales graves, disfunción de mitocondrias, y como consecuencia, inhibe la proliferación celular por acumulación de daños en mitocondrias, causa un aumento de la senescencia celular en cultivos de fi broblastos de ratón (Hu et al 2017). El efecto tóxico de fl orfenicol sobre el cloroplasto, produce inhibición del crecimiento de cultivos de microalgas (Chlorella pyrenoidosa, Isochrysis galbana y Tetraselmis chui) (Wang et al 2015;Du & Liu 2012;Lai et al 2009), inhibiendo la fotosíntesis en Skeletonema costatum, a una concentración mayor o igual a 1 mg/L en 6 h (Liu et al 2012).…”
Section: Discussionunclassified
“…EdU, which is a rather new thymidine analog that can be incorporated into DNA during active DNA synthesis, has widely been used to trace the cell proliferation ability [21]. In this study, subconfluent preadipocytes were treated with different SB doses for 24 h. Then, the cells were incubated with 10 µM EdU for 2 h. Cell increment could be detected via a chemical reaction with Andy FluorTM 488 Azide (green fluorescence).…”
Section: Edu and Cck-8 Assaysmentioning
confidence: 99%